Accelerating Li+ recovery kinetics of 5TiO2·2H2O adsorbents from original geothermal water by configuring TiO2·H2O phase - Lin Jing; Chunxi Hai; Xuemei Zuo; Lijuan Zhang; Shengde Dong; Yanxia Sun; Luxiang Ma; Qi Xu; Xin He; Yuan Zhou (Desalination, 2026)

Transformation of crop structure intensified extreme drought shocks to prehistoric settlements: an integrated study of lacustrine sediments and environmental archaeology in southwestern China - Tao Wang; Duo Wu; Zehui Li; Qili Xiao; Dan Luo; Shilong Guo; Lili Pan; Lin Chen; Yongxiu Lu; Shuai Shao; Zijie Yuan; Peiyao Xu; et al. (Global and Planetary Change, 2026)

Molecular characterization and preliminary functional analysis of the NLRP3 inflammasome in golden pompano (Trachinotus ovatus) in response to Streptococcus agalactiae infection - Zhengjing Lin; Xuemei Mou; Peng Xu; Kianann Tan; Ting Huang; Renjie Li; Shuo Hu; Xiaoxin Huang; Sisi Huang; Lanfang Dong; Xiaohui Cai (Fish & Shellfish Immunology, 2026)

Enriched microplastic-associated biofilms exacerbate gut microbial dysbiosis and metabolic disruption in mice - Shan Li; Tingqin Chen; Jiajia Liu; Kunman Lu; Xuemei Chen; Lianbing Lin; Yicen Lin (Environmental Pollution, 2026)

Sediment pore-network architecture may shape spatial patterns of denitrification in freshwater littoral zones - Xuemei Zhao; Yi Zhu; Weijie Lin; Fangyu Liu; Xuan Huang; Huan Fang; Dongli She; Xiaoqin Sun; Yongqiu Xia (Water Research, 2026)

Size matching between laccase and carrier via tunable diamine-derived flexible spacer arms for enhanced phenolic wastewater degradation - Jie Zhang; Yiqi Gong; Zhipeng Qin; Xinyi Liu; Jiao Yu; Tao Feng; Wan Zhang; Wenjing Lin; Kaiyue Kang; Xuemei Tan; Lin Zhuo; Ruiqi Wang; et al. (Journal of Water Process Engineering, 2026)

Density functional theory-assisted: In-situ growth of NH2-UiO-66 on polypyrrole for high-selectivity electrochemical detection of nitrophenol isomers - Xuemei Wang; Rao Peng; Lin Fan; Yi Song; Shujie Wang; Xinzhen Du; Xiaoquan Lu (Analytica Chimica Acta, 2026)

Comparative evaluation of a fast in-situ droplet detector and water-sensitive paper for pesticide spray distribution assessment in crop protection operations - Shihui Yu; Jian Liu; Xianguo Huang; Lin Liu; Xuemei Liu; Zhenbo Xin; Jin Yuan; Geoffrey I.N. Waterhouse (Crop Protection, 2026)

A combined hazard to mariculture: Quality and safety impairment associated with intestinal barrier disruption in fish co-exposed to environmentally relevant microplastics and antibiotics - Lin Zhu; Changlong Cui; Ying Bai; Xuemei Sun; Qi Sui; Nurzafirah Mazlan; Bin Xia (Journal of Hazardous Materials, 2026)

Occurrence and leaching of per- and polyfluoroalkyl substances in waste incineration residues: Insights into thermodynamic mechanisms and implications for environmental release - Lanlan Fu; Xingyao Huang; Xuemei Liu; Nan Zhang; Rui Ma; Xinyue Wang; Yue Zhi; Lin Li; Xiaoming Wang (Journal of Hazardous Materials, 2026)

LandslideSegFormer: A non-local context-aware dual-branch network for accurate small-scale landslide segmentation from remote sensing imagery - Xuemei Lee; Lin Bai; Dinghong Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Coupling upconversion effect with p-n heterojunction on TiAl6V4 to eradicate bacterial biofilms - Keyi Yao; Lixuan Huang; Jie Shao; Junyu Dong; Junhua Xu; Yongsheng Liu; Sze Wing Cheung; Lin Xiang; Xuemei Zhou (Chemical Engineering Journal, 2026)

The associations between prenatal greenness exposure and neurodevelopment in early childhood: A birth cohort study - Zhen Wang; Xiaoxu Li; Weiyin Zhuang; Xuemei Liu; Xiuxiu Li; Lin Guo; Mengfan Li; Lizi Lin; Li Cai (Urban Forestry & Urban Greening, 2026)

Phosphorylation-modified fava bean 11S protein fibril-based oleogels: A novel strategy to enhance network flexibility and alter rheological and textural properties - Zhihao Xu; Xuemei Lin; Wenzhong Zhao; Xiaoqi Ding; Xianglin Sun; Yuting Ding; Hui Chen; Pengbo Cui (Food Hydrocolloids, 2026)

16S rDNA sequencing combined with non-targeted metabolomics profiling reveals the mechanism of simulated digestion ultra-sound pea protein isolate in vitro - Xinyu Zhao; Xuemei Dong; Jianke Fang; Chun Li; Lin Zhao; Guofang Zhang; Peng Du; Tong Zhang; Xinyao Sun; Libo Liu; Wenkui Guo (Food Bioscience, 2026)

Probabilistic risk assessment of heavy metal(loid)s in traditional Chinese medicinal materials and their decoctions: Integrating dissolution characteristic with Monte Carlo simulation - Guanjun Nan; Zhengzheng Liu; Xuemei Zhou; Yunzhe Li; Fanli Yang; Rong Lin; Guangde Yang (Food and Chemical Toxicology, 2026)

A “three birds with one stone” strategy: Light-switchable chitosan film via natural supramolecular co-assembly for enhanced fruit preservation - Zhiwei Wang; Jihui Lu; Jichang Wei; Yihang Zhao; Yiqing Huang; Shuchang Yao; Xinru Tan; Xiaoyu Lin; Xuemei Huang; Penglong Wang (Chemical Engineering Journal, 2026)

Widely targeted metabolomics of Salix songarica flowers: impact of drying methods on flavonoid profiles and antioxidant capacity - Xuemei Dai; Kaili Zhang; Zhuo Yao; Hao Li; Ruixin Lin; Wenwen Zhang; Yunhua Hu; Haixia Wang; Shangzhi Xu; Li Zhang (Food Bioscience, 2026)

Ocean acidification enhances TiO2 nanoparticle toxicity in Oryzias melastigma: Dominant role of size effects in driving bioaccumulation and hepatotoxicity - Lin Zhu; Li Zou; Mengchen Nie; Bin Xia; Jian Zhao; Qi Sui; Xuemei Sun; Baoshan Xing (Water Research, 2026)

Functional characterization of PsnErf1b in regulating salt stress tolerance in poplar - Zihan Cheng; Xinyu He; Xinyue Tu; Haiyan Fang; Lin Liu; Tingbo Jiang; Xuemei Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Climate-driven perturbations on land emissions and deposition of atmospheric nitrogen - Xuemei Wang; Lin Zhang; Jialin Deng; Min Shao (Science Bulletin, 2025)

Potential disease-related risk of saccharin in ovarian cancer: An integrative multi-evidence analysis - Yang Song; Hao Yang; Yanchun Wang; Chenchen Lin; Xuemei Wang (Reproductive Toxicology, 2025)

Relating small waterbody denitrification with ecosystem respiration in an intensive anthropogenic region - Xuemei Zhao; Yi Zhu; Xu Yang; Li Zhang; Xuan Huang; Chunwang Li; Kebing Chen; Han Lin; Dongli She; Yongqiu Xia (Journal of Hydrology, 2025)

Plateau-specific atmosphere amplifies fuel evaporative emission in Tibet: A case study of Lhasa - Zhouyue Lin; Xuemei Yang; Tsring Nyixia; Minhan Zhang; Yuefu Yuan; Wei Wei (Journal of Environmental Sciences, 2025)

Synergistic exposure to endocrine-disrupting chemicals in pediatric lungs: Epidemiological drivers and disease-associated variations - Chunzhao Chen; Jie Yu; Hui Qi; Cuiying Zhong; Jian Tang; Chenghao Chen; Zheng Li; Xuemei Yang; Yujia Wu; Wanning Chen; Gang Yu; Lin Sun (Environmental Pollution, 2025)

A major and stable QTL confers impatiens necrotic spot virus resistance in lettuce cv. Eruption - Santosh Nayak; Kelley L. Richardson; Renée L. Eriksen; Daniel K. Hasegawa; William M. Wintermantel; Manoj Sapkota; Xuemei Tang; Shufen Chen; Meng Lin; Dongyan Zhao; Craig T. Beil; Moira J. Sheehan; et al. (Theoretical and Applied Genetics, 2025)
Key message A large effect and environmentally stable QTL was identified on LG2 that confers high levels of INSV resistance in lettuce cultivar Eruption. Abstract Impatiens necrotic spot virus (INSV) has recently emerged as a major threat to lettuce production in the Salinas Valley of California, the region which contributes over 60% of the US national supply. This thrips-transmitted virus can infect lettuce plants at any growth stage, causing premature death or a total loss of marketability. Both INSV and its thrips vector have broad host ranges, which complicate disease management. Utilizing genetic resistance is the most sustainable approach; however, complete immunity has not been identified and the genetic basis of resistance to INSV in lettuce remains poorly understood. This study aimed to identify quantitative trait loci (QTL) and elucidate the underlying mechanism of INSV resistance in ‘Eruption,’ a lettuce cultivar exhibiting highly stable partial resistance across environments. Using 162 F 6:8 recombinant inbred lines (RILs) developed from a cross between moderately susceptible ‘Reine des Glaces’ and ‘Eruption,’ and a genetic linkage map comprising 1598 single nucleotide polymorphism (SNP) markers, phenotypic data collected from field and greenhouse experiments consistently revealed a highly significant, major QTL on linkage group 2. This QTL exhibited partial dominance with additive effects, explaining up to 61% of the total phenotypic variation for INSV disease severity. Furthermore, INSV resistance was found to be highly heritable, with heritability estimates of up to 0.89, indicating strong genetic control. Results of this study are crucial for fine mapping and the development of marker-assisted selection assays to accelerate the breeding of more advanced INSV-resistant lettuce cultivars.

Critical Buffer Zones (500–1000 m) for River Ecosystem Integrity: Scale-Dependent Land Use Impacts on Macrobenthos in the Tanghe River, China - Xiaoyue Lin; Xuemei Han; Jiading Yang; Fengyu Liu; Shujia Chang (International Journal of Environmental Research, 2025)

Influence of eco-friendly float replacement on microplastic pollution and their metal adsorption behavior in Sanggou Bay, China - Qi Sui; Hao Wang; Guoshun Liu; Xiaoli Chen; Xuemei Sun; Lin Zhu; Manman Wei; Zhihua Feng; Bin Xia (Marine Environmental Research, 2025)

Bioaccumulation, biomagnification and ecological risk evaluation of microplastics in Sanggou Bay, China - Qi Sui; Xuemei Sun; Lin Zhu; Shunlong Meng; Bin Xia (Journal of Hazardous Materials, 2025)

High altitude-induced aggravation of road vehicle emissions was studied and estimated in Lhasa, the capital of Tibet - Xuemei Yang; Minhan Zhang; Zhouyue Lin; Tsring Nyixia; Yangjin Lamu; Wei Wei (Environmental Research, 2025)

Regulating the coordination distance of solvation structure for high-performance aqueous zinc ion batteries - Yijia Luo; Chao Li; Lieyuan Zhang; Xin Tan; Yi Yang; Bin Xie; Dandan Zhang; Haoran Lang; Xingyu Chen; Xuemei He; Qiaoji Zheng; Xinqiao Wu; et al. (Chemical Engineering Journal, 2025)

Defect-engineered heterostructured NiFe-LDH@CoNi-LDH nanocages via synergistic interface-oxygen vacancy modulation for high-energy-density supercapacitors - Wenxiao Zhang; Ziyang Zhu; Lin Zhu; Xiaohui Xu; Xuemei Chen; Xinyan Wang; Min Lu (Chemical Engineering Journal, 2025)

Disparities in heat exposure between urban and rural populations: A case study of the Yangtze River Delta - Jin Lin; Guofu Yang; Wenbin Nie; Zhenguo Wang; Hao Chen; Xuemei Pan; Yaxin Zhou; Liwei Pang; Bin Xu (Sustainable Cities and Society, 2025)

Potential impact of marine-derived plastisphere as a Vibrio carrier on marine ecosystems: Current status and future perspectives - Xuemei Sun; Andy M. Booth; Qi Sui; Lin Zhu; Yongxiang Yu; Bin Xia; Shunlong Meng; Baoshan Xing (Journal of Hazardous Materials, 2025)

Enhanced biosynthesis of 6-aminocaproic acid in engineered Escherichia coli with artificial protein cage-organized enzymatic cascades - Ruoshi Luo; Lin Hu; Dan Wang; Kaixing Xiao; Xuemei Liu; Yaqi Kang; Qinhong Wang (Bioresource Technology, 2025)

Impact of annual plant prevalence on soil carbon storage through root turnover and productivity - Yajie Zhang; Tao Zhou; Jingyu Zeng; E Tan; Jingzhou Zhang; Xuemei Wu; Qiaoyu Lin; Qi Zhang; Xia Liu; Yixin Xu; Bowen Liu (Plant and Soil, 2025)

Occurrence, trophic transfer and risk assessment of microplastics in fishery organisms from the Bohai Sea, China - Qilong Li; Lin Zhu; Xiaoying Pu; Qi Sui; Xuemei Sun; Xinguo Zhao; Rongyuan Wang; Bin Xia (Journal of Hazardous Materials, 2025)

Rapid reduction of nitrate to nitrogen gas by the synergistic effect of KBH4 with copper loaded polyaniline carbon nanotube composite - Aijuan Zhou; Xin Lin; Xuemei Zhang; Jing Chen; Li Cai; Chenxi Wu; Yong Liu (Journal of Environmental Chemical Engineering, 2025)

Provenance of the detrital deposits in the Daju Basin of the Jinsha River, China - Lingling Li; Weiming Liu; Xu Lin; Anna Yang; Xuemei Li; Zewen Yang; Huimin Zhao (Journal of Geographical Sciences, 2025)

A Sandwich‐Like Pattern of Eastern China Summer Precipitation Change Projected by CMIP6 Models - Xuemei Liu; Lu Wang; Xiaolong Chen; Lin Chen (International Journal of Climatology, 2025)
A reliable projection of the summer (June–August) mean precipitation over eastern China (EC) in the future is crucial for climate adaptation activities in this densely populated region. In contrast to existing studies, which have primarily focused on the EC mean precipitation change and have demonstrated a wetting trend in the future, this study, based on an analysis of 35 Coupled Model Intercomparison Project Phase 6 models, highlights that the future precipitation rise within the EC area is distributed inhomogeneously with latitudes. The southern and northern EC regions are projected to experience a pronounced increase in precipitation, while the middle EC, where the well‐known meiyu‐baiu rainbelt is located, is expected to witness a comparatively weaker rise. This sandwich‐like pattern is consistent across models and is evident irrespective of future periods and greenhouse‐gas‐emission scenarios specified. The findings have significant implications for the future management of water resources along China's major rivers, which are all located within the EC. Further analysis of the moisture budget indicates that the dynamical response to global warming is the key driver of this sandwich‐like pattern of precipitation change. The relatively weak precipitation increase over the central EC is attributed to the eastward retreat of the western North Pacific subtropical high (WNPSH) in the future, while a more pronounced precipitation increase over the northern EC is related to the enhanced southerly wind along the eastern coast of China.

Organic matter components rather than microbial enzymes and genes predominate CO2/CH4 emissions during composting amended with biochar at different stages - Sijia Gu; Zhanglong Ji; Xuemei Li; Hao Qin; Maosheng Li; Lihua Zhang; Jiachao Zhang; Hongli Huang; Lin Luo (Environmental Pollution, 2025)

Microplastics enhance laccase-driven bisphenol A removal in multipollutant wastewater - Jie Zhang; Jiongna Liu; Xinyi Liu; Yu Su; Chunyang Yu; Xuemei Tan; Lin Zhuo; Mei Ye; Qinglin Luo; Biao Li (Journal of Environmental Management, 2025)

Systematical identification of regulatory GPCRs by single-cell trajectory inference reveals the role of ADGRD1 and GPR39 in adipogenesis - Chuan Ye; Xuemei Wang; Jun Lin; Chenyang Wu; Yuhua Gao; Chenghao Guo; Yunxi Liao; Ziyan Rao; Shaodong Huang; Weixuan Chen; Ying Huang; Jinpeng Sun; et al. (Science China Life Sciences, 2025)

Preface to the Special Topic on Air Pollution Complex Research in China: Recent Advances - Tong Zhu; Mingjin Tang; Hong Liao; Yele Sun; Lin Wang; Minghuai Wang; Xuemei Wang (Advances in Atmospheric Sciences, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Thiostrepton suppresses colorectal cancer progression through reactive oxygen species related endoplasmic reticulum stress - Zhexuan Li; Juan Nie; Runyu Zhou; Hui Huang; Xuemei Li; Li Wang; Lin Lv; Sichong Ren; Ming Zhao (Toxicology and Applied Pharmacology, 2025)

Effect of salt-induced supercooling stability on the quality of chicken breast during supercooled storage - Yiping Yang; Hengxun Lin; Yong Chen; Liye Cui; Hongliang Li; Shuangmei Xia; Chunhui Zhang; Junrong Huang; Hui Zhang; Jiansheng He; Xuemei Sun; Xia Li (Food Control, 2025)

Association of early life exposure to PM2.5 and its components with offspring neurodevelopment: A prospective birth cohort study - Yuchuan Deng; Xiaoxu Li; Xiuxiu Li; Xuemei Liu; Lizi Lin; Li Cai; Min Zhang (Environmental Research, 2025)

Genetic characterization of a novel HIV-1 circulating recombinant form (CRF162_cpx) involving CRF01_AE, CRF07_BC and subtype B in Guangdong, China - Yun Lan; Linghua Li; Mingfeng Xiao; Yaqing Lin; Xuemei Ling; Feng Li; Fengyu Hu (Virus Genes, 2025)

Cross-Scale Quantitative and Qualitative Study of Grotto Sandstone Under Salt Weathering - Sicheng Lin; Luqi Wang; Wengang Zhang; Shuo Wang; Kaiqiang Zhang; Yu Lei; Siwei Jiang; Huili Chen; Gang Zhao; Xuemei Feng (Rock Mechanics and Rock Engineering, 2024)

Greening the marine map: a comprehensive study of China’s marine ecological and economic synergy - Zechen Li; Hanqian Lin; Xuemei Zhang (Frontiers in Marine Science, 2024)
Introduction This research examines the coupling coordinated development dynamics between marine ecological governance and marine economic development in China’s coastal provinces. The marine ecological governance and economic development data of China’s 11 coastal provinces were comprehensively analyzed from 2011 to 2021. Methods We established a multi-dimensional evaluation index system for marine ecological governance and economic development, employing the global entropy weight method for quantification. Furthermore, the research examines and analyzes the trends in coordinated development and divergence between these two systems by constructing a coupled coordination degree(CCD) model, utilizing the Theil index decomposition method, and employing the geodetector detector. Results The Northern marine economic circle outperforms the Eastern and Southern ones regarding marine ecological governance, while the Eastern marine economic circle is the most advanced in marine economic development. The results of the CCD model indicate that Guangdong, Shandong, Hebei, and Jiangsu have the best coupling coordinated development, while Hainan, Tianjin, and Guangxi are at the bottom. The results of the Theil index decomposition method indicate that intra-regional disparities are the primary cause of coupling coordinated regional development variations. At the same time, the results of the geographic detector further substantiate that energy structure, degree of industrial agglomeration, and foreign overseas direct investment are the principal influencing factors. Discussion The study presents policy recommendations derived from the findings intended to foster the integrated advancement of marine ecology and economy in coastal provinces, reduce regional development disparities, and establish a scientific foundation for achieving a sustainable marine economy.

ReYOLO-MSM: A novel evaluation method of mushroom stick for selective harvesting of shiitake mushroom sticks - Kai Tao; Jian Liu; Zinuo Wang; Jin Yuan; Lin Liu; Xuemei Liu (Computers and Electronics in Agriculture, 2024)

Distinct roles of H3K27me3 and H3K36me3 in vernalization response, maintenance, and resetting in winter wheat - Xuemei Liu; Min Deng; Bingxin Shi; Kehui Zhu; Jinchao Chen; Shujuan Xu; Xiaomin Bie; Xiansheng Zhang; Xuelei Lin; Jun Xiao (Science China Life Sciences, 2024)

Global research trends in Rhizodeposition-mediated soil carbon cycle: A bibliometric analysis - Dongming Chen; Fei Yan; Xuemei Fang; Jiqiong Zhou; Xingpeng Hu; Xiaoming Ma; Xin Zheng; Rui Yin; Feida Sun; Yanfu Bai; Zhouwen Ma; Yakov Kuzyakov; et al. (Applied Soil Ecology, 2024)

Rac1 promotes the lipopolysaccharide-induced inflammatory response and contraction-associated proteins (CAPs) expression in mouse uterine smooth muscle cells - Min Diao; Yunkai Tao; Qian Liu; Lu Huang; Hao Li; Xuemei Lin (Reproductive Biology, 2024)

Mixing with Schima Superba Enhanced Soil Fertility and Simplified Soil Microbial Community of Eucalyptus Urophylla Forests - Wentao Hu; Jinrui Chen; Mengyao Liu; Xueqin Tian; Xuemei Chen; Wei Lin; Zuying Xuan; Lan Pan (Journal of Soil Science and Plant Nutrition, 2024)

Insight into mitigation mechanisms of N2O emission by biochar during agricultural waste composting - Jun Liu; Yunlong Hu; Sijia Gu; Xuemei Li; Zhanglong Ji; Hao Qin; Lihua Zhang; Jiachao Zhang; Hongli Huang; Binghua Yan; Lin Luo (Bioresource Technology, 2024)

Honeycomb-like triazine-based conjugated microporous polymers exhibiting simultaneous and ultrasensitive detection of fifteen polycyclic aromatic hydrocarbons using solid-phase microextraction technique - Xinzhong Zhang; Hong Ji; Xuemei Wang; Lin Fan; Jingwei Liu; Wen Zhang; Xinzhen Du; Xiaoquan Lu (Analytica Chimica Acta, 2024)

Combined toxicity of polyvinyl chloride microplastics and copper to marine jacopever (Sebastes schlegelii) - Zike Li; Meijing Zhao; Zhihua Feng; Lin Zhu; Qi Sui; Xuemei Sun; Bin Xia (Marine Environmental Research, 2024)

Bioaccumulation of polycyclic aromatic hydrocarbons and their human health risks depend on the characteristics of microplastics in marine organisms of Sanggou Bay, China - Qi Sui; Xiaobin Yang; Xuemei Sun; Lin Zhu; Xinguo Zhao; Zhihua Feng; Bin Xia; Keming Qu (Journal of Hazardous Materials, 2024)

Metabolome and transcriptome reveal high abundance of bioactive substances in albino jujube fruit as potential function food - Yang Wang; Yong Huang; Panhui Song; Xuemei Peng; Xinyu Li; Rong Su; Hui Zhang; Lijin Lin; Hui Xia; Qunxian Deng (Food Bioscience, 2024)

Kidney Function and Cardiovascular Disease: Evidence from Observational Studies and Mendelian Randomization Analyses - Wenjun Yang; Xuemei Wu; Manying Zhao; Jianying Hu; Chenhao Lin; Zhendong Mei; Jing Chen; Xu-jie Zhou; Sheng Nie; Jing Nie; Xiang Gao; Yan Zheng; et al. (Phenomics, 2024)

Regulated Necrosis in Glaucoma: Focus on Ferroptosis and Pyroptosis - Duan Chen; Sen Miao; Xuemei Chen; Zhiyi Wang; Pei Lin; Ningzhi Zhang; Ning Yang (Molecular Neurobiology, 2024)

Review of transpired solar collectors: Heat and mass transfer mechanisms and enhancement, system integration, and performance assessment and optimisation - Shengteng Li; Xuemei Gong; Wenye Lin; Yongjun Sun; Zhenjun Ma (Journal of Cleaner Production, 2024)

Temperature sensitivity of soil-borne fungal phytopathogens depends on niche breadth and land use types - Bangguo Yan; Yi Sun; Guangxiong He; Xuemei Wang; Lin Li; Xuewen Yue; Liangtao Shi; Haidong Fang (Fungal Ecology, 2024)

Association of residential greenness, air pollution with adverse birth outcomes: Results from 61,762 mother‑neonatal pairs in project ELEFANT (2011–2021) - Yuanyuan Yu; Huishu Lin; Qisijing Liu; Yuxuan Ma; Lei Zhao; Weixia Li; Yan Zhou; Hyang-Min Byun; Penghui Li; Chen Li; Congcong Sun; Xuemei Chen; et al. (Science of The Total Environment, 2024)

Physiological and transcriptomic analysis reveals the toxic and protective mechanisms of marine microalga Chlorella pyrenoidosa in response to TiO2 nanoparticles and UV-B radiation - Lin Zhu; Sulan Feng; Yu Li; Xuemei Sun; Qi Sui; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2024)

Polystyrene nanoplastics affected the nutritional quality of Chlamys farreri through disturbing the function of gills and physiological metabolism: Comparison with microplastics - Yejiao Sun; Xinguo Zhao; Qi Sui; Xuemei Sun; Lin Zhu; Andy M. Booth; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Central retinal artery occlusion caused by radiation-induced carotid stenosis - Qingli Lu; Xiangning Han; Pei Liu; Xuemei Lin; Songdi Wu (Acta Neurologica Belgica, 2024)

Crucial roles of the optimal time-scale of water condition on grassland biomass estimation on Qinghai–Tibet Plateau - Yajie Zhang; Tao Zhou; Xia Liu; Jingzhou Zhang; Yixin Xu; Jingyu Zeng; Xuemei Wu; Qiaoyu Lin (Science of The Total Environment, 2023)

New insights into the impact of polystyrene micro/nanoplastics on the nutritional quality of marine jacopever (Sebastes schlegelii) - Xuemei Sun; Xuru Wang; Andy M. Booth; Lin Zhu; Qi Sui; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2023)

Complete genome sequence of Paris polyphylla chlorotic mottle virus infecting Paris polyphylla var. yunnanensis in southwest China - Qiongji He; Binghua Chen; Hongying Zheng; Yuhao Cao; Mengyin Hua; Yueyan Yin; Jiejun Peng; Junmin Li; Jianping Chen; Fei Yan; Xuemei Song; Lin Lin (Archives of Virology, 2023)

Simultaneous enhancement on lignocellulose degradation and humic acid formation using the electric field coupled with an iron anode in the co-composting of food waste and agricultural waste - Yingying He; Rujing Lin; Xuemei Yu; Yike Ma; Jialu Li; Li Xie (Chemical Engineering Journal, 2023)

Molecular Cloning and Expression Analysis of Lipoprotein Lipase (LPL) From Pampus Argenteus - Shun Zhang; Mengdi Liu; Xiaojing Zhu; Chuangyuan Lin; Cheng Zhang; Xuemei Yan; Danli Wang; Shanliang Xu (Thalassas: An International Journal of Marine Sciences, 2023)

Performance and mechanism of calcium peroxide reducing H2S production from sludge anaerobic fermentation - Yunhao Xu; Qizi Fu; Wenming Wang; Fan Yang; Xuemei Li; Fengming Song; Yanguang Qing; Ziqi Lin; Weiqi Long; Dongbo Wang (Chemical Engineering Journal, 2023)

Analysis of retest reliability for pregnant women undergoing cfDNA testing with a no-call result - Shuqiong He; Qian Zhang; Meihuan Chen; Xuemei Chen; Bin Liang; Na Lin; Hailong Huang; Liangpu Xu (Molecular Biology Reports, 2023)
Background Determining the reasons for unreportable or no-call cell-free DNA (cfDNA) test results has been an ongoing issue, and a consensus on subsequent management is still lacking. This study aimed to explore potential factors related to no-call cfDNA test results and to discuss whether retest results are reliable. Methods and results This was a retrospective study of women with singleton pregnancies undergoing cfDNA testing in 2021. Of the 9871 pregnant patients undergoing cfDNA testing, 111 had a no-call result, and their results were compared to those of 170 control patients. The no-call rate was 1.12% (111/9871), and the primary cause for no-call results was data fluctuation (88.29%, 98/111). Medical conditions were significantly more frequent in the no-call group than in the reportable results group (P < 0.001). After retesting, 107 (107/111, 96.40%) patients had a result, and the false-positive rate (FPR) of retesting was 10.09% (10.09%, 11/109). In addition, placental lesions were more frequent in the no-call group than in the reportable results group (P = 0.037), and 4 patients, all in the no-call group, experienced pregnancy loss. Conclusions Pregnant women with medical conditions are more likely to have a no-call result. A retest is suggested for patients with a no-call result, but retests have a high FPR. In addition, pregnant women with a no-call result are at increased risk of adverse pregnancy outcomes. In conclusion, more attention should be given to pregnant women for whom a no-call cfDNA result is obtained.

Irisin protects against doxorubicin-induced cardiotoxicity by improving AMPK-Nrf2 dependent mitochondrial fusion and strengthening endogenous anti-oxidant defense mechanisms - Caili Zhuo; Juanjuan Xin; Wenjing Huang; Die Zhang; Xin Yan; Ruli Li; He Li; Jie Lan; Lan Lin; Lingyu Li; Xuemei Wang; Linling Liu; et al. (Toxicology, 2023)

Green space exposure on depression and anxiety outcomes: A meta-analysis - Ziquan Liu; Xuemei Chen; Huanhuan Cui; Yuxuan Ma; Ning Gao; Xinyu Li; Xiangyan Meng; Huishu Lin; Halidan Abudou; Liqiong Guo; Qisijing Liu (Environmental Research, 2023)

Connecting the Gut Microbiota and Neurodegenerative Diseases: the Role of Bile Acids - Shixu Wang; Chongchong Xu; Hongyan Liu; Wei Wei; Xuemei Zhou; Haipeng Qian; Li Zhou; Haiqing Zhang; Li Wu; Chen Zhu; Yuting Yang; Lin He; et al. (Molecular Neurobiology, 2023)

Impact of Cold Spells on Ischemic Stroke Severity and Clinical Outcomes in Tianjin, China - Juanjuan Xue; Chanjuan Wei; Xiaoshuang Xia; Xuemei Qi; Yumeng Gu; Zhongyan Wang; Suqin Han; Lin Wang; Xin Li (Journal of Meteorological Research, 2023)

Ocean acidification enhances the embryotoxicity of CuO nanoparticles to Oryzias melastigma - Hao Wang; Qi Sui; Jian Zhao; Xuemei Sun; Lin Zhu; Bijuan Chen; Keming Qu; Bin Xia (Journal of Hazardous Materials, 2023)

Knowledge Map and Global Trends in Root Exudates Research from 2012 to 2021: a Bibliometric Analysis - Xin Zheng; Dongming Chen; Jiqiong Zhou; Qian Huang; Xingpeng Hu; Zhuxin Deng; Xuemei Fang; Feida Sun; Junming Zhao; Xiao Ma; Congyu Ma; Xinrui Yan; et al. (Journal of Soil Science and Plant Nutrition, 2023)

Long-term exposure to ambient air pollutants and their interaction with physical activity on insomnia: A prospective cohort study - Yijuan Lin; Yinyan Gao; Xuemei Sun; Jiali Wang; Shuzi Ye; Irene X.Y. Wu; Fang Xiao (Environmental Research, 2023)

A RNAi-based strategy to suppress Micropterus salmoides rhabdovirus in GCO cells and largemouth bass by silencing envelope glycoprotein - Xuemei Yuan; Jiayun Yao; Lei Huang; Lingyun Lin; Xiaoyi Pan; Jinbiao Jiao; Haiqi Zhang (Aquaculture, 2023)

Charge-dependent negative effects of polystyrene nanoplastics on Oryzias melastigma under ocean acidification conditions - Yufei Chen; Xia Wang; Qi Sui; Guozhu Chang; Xuemei Sun; Lin Zhu; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2023)

Development of structural equation models to unveil source-sink switches of mid-latitude soils for semi-volatile banned pesticides - Qian Li; Lin Cai; Rubing Wang; Chunlong Xia; Guoqing Cui; Cong Li; Xuemei Zheng; Xiyun Cai (Environmental Pollution, 2023)

Aqueous-phase chemistry of atmospheric phenolic compounds: A critical review of laboratory studies - Fenghua Li; Shengzhen Zhou; Lin Du; Jun Zhao; Jian Hang; Xuemei Wang (Science of The Total Environment, 2023)

CircCERS6 Suppresses the Development of Epithelial Ovarian Cancer Through Mediating miR-630/RASSF8 - Xiaoqin Li; Xuemei Jiang; Jing Lu; Yuting Lin; Lan Jiang; Yan Li; Feng Wan; Changmin Wang (Biochemical Genetics, 2022)

NAD+-capped RNAs are widespread in rice (Oryza sativa) and spatiotemporally modulated during development - Haijiao Dong; Xufeng Wang; Cong Tan; Lei Gao; Jie Cui; Lin Liu; Beixin Mo; Yongzhong Xing; Yu Yu; Xuemei Chen (Science China Life Sciences, 2022)

Ecological risk assessment of metallic nanoparticles on the marine environments: Species sensitivity distributions analysis - Sulan Feng; Lin Zhu; Xinguo Zhao; Qi Sui; Xuemei Sun; Bijuan Chen; Keming Qu; Bin Xia (Frontiers in Marine Science, 2022)
Metallic nanoparticles (NPs) are increasingly being used and inevitably entering the marine environment. Therefore, the adverse effects of NPs on individual marine species have attracted increasing attentions. However, to date, the ecological risks of NPs on the marine ecosystem remain poorly understood. In this study, species sensitivity distributions (SSDs) were constructed for Ag, ZnO, CuO, and TiO 2 NPs to understand their ecotoxicity to the marine ecosystem and the contribution of size effect and ion effect to the nanotoxicity. Furthermore, a case study on the assessment of marine ecological risk and marine environment carrying capacity of metallic NPs was performed in Jiaozhou Bay, China. The results showed the toxicity of metallic NPs to marine species following the order of Ag > ZnO > CuO > TiO 2 . Both size effect and ion effect contributed to the toxicity of NPs. Environmental concentrations of Ag, ZnO, CuO, and TiO 2 NPs are much lower than the predicted no-effect concentrations, indicating that these metallic NPs have not yet posed risks to the marine ecosystem based on currently limited measured environmental concentrations of metallic NPs in seawater. And the marine environment carrying capacity of Ag, ZnO, CuO, and TiO 2 NPs in Jiaozhou Bay seawater were determined to be 5.03, 8.72, 93.06, and 629.79 t, respectively. The results help us understand the ecological risk of NPs in marine environments and provide a scientific basis for the sustainable development of nanotechnology.

Salicylic acid alleviates selenium stress and promotes selenium uptake of grapevine - Zhiyu Li; Rong Fan; Xuemei Peng; Junjiang Shu; Lei Liu; Jin Wang; Lijin Lin (Physiology and Molecular Biology of Plants, 2022)

Mussel Byssal Attachment Weakened by Anthropogenic Noise - Xinguo Zhao; Shuge Sun; Wei Shi; Xuemei Sun; Yan Zhang; Lin Zhu; Qi Sui; Bin Xia; Keming Qu; Bijuan Chen; Guangxu Liu (Frontiers in Marine Science, 2021)
The increasing underwater noise generated by anthropogenic activities has been widely recognized as a significant and pervasive pollution in the marine environment. Marine mussels are a family of sessile bivalves that attach to solid surfaces via the byssal threads. They are widely distributed along worldwide coastal areas and are of great ecological and socio-economic importance. Studies found that anthropogenic noise negatively affected many biological processes and/or functions of marine organisms. However, to date, the potential impacts of anthropogenic noise on mussel byssal attachment remain unknown. Here, the thick shell mussels Mytilus coruscus were exposed to an ambient underwater condition (∼50 dB re 1 μPa) or the playbacks of pile-driving noise (∼70 or ∼100 dB re 1 μPa) for 10 days. Results showed that the noise significantly reduced the secretion of byssal threads (e.g., diameter and volume) and weakened their mechanical performances (e.g., strength, extensibility, breaking stress, toughness and failure location), leading to a 16.95–44.50% decrease in mussel byssal attachment strength. The noise also significantly down-regulated the genes expressions of seven structural proteins (e.g., mfp-1, mfp-2, mfp-3, mfp-6, preCOL-P, preCOL-NG, and preCOL-D) of byssal threads, probably mediating the weakened byssal attachment. Given the essential functions of strong byssal attachment, the findings demonstrate that the increasing underwater anthropogenic noise are posing a great threat to mussel population, mussel-bed community and mussel aquaculture industry. We thus suggest that future work is required to deepen our understanding of the impacts of anthropogenic noise on marine invertebrates, especially these with limited locomotion ability, like bivalves.

Molecular Cloning and Characterization of FAD6 Gene from Chia (Salvia hispanica L.) - Yufei Xue; Lejing Li; Xuemei Liu; Huanhuan Jiang; Yanping Zhao; Songzhen Wei; Na Lin; Yourong Chai (Biochemical Genetics, 2021)

Molecular cloning and characterization of two plastidial Δ12 fatty acid desaturase cDNAs from Perilla frutescens - Yufei Xue; Huanhuan Jiang; Baojun Chen; Jiayi Jiang; Na Lin; Lejing Li; Xuemei Liu; Yourong Chai (Acta Physiologiae Plantarum, 2021)

Complete genome sequence of passiflora virus Y infecting passion fruit in China - Binghua Chen; Dali Wu; Hongying Zheng; Guangze Li; Yuhao Cao; Jianping Chen; Fei Yan; Xuemei Song; Lin Lin (Archives of Virology, 2021)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

Mechanical properties of soft soils experiencing lateral unloading under initial excess pore water pressure - Wei Huang; Kejun Wen; Junjie Li; Xuemei Fu; Shihui Liu; Yang Li; Lin Li; Farshad Amini (Arabian Journal of Geosciences, 2020)

Advances in Urban Meteorological Research in China - Shiguang Miao; Weimei Jiang; Ping Liang; Hongnian Liu; Xuemei Wang; Jianguo Tan; Ning Zhang; Ju Li; Wupeng Du; Lin Pei (Journal of Meteorological Research, 2020)

The Glutamatergic Postrhinal Cortex–Ventrolateral Orbitofrontal Cortex Pathway Regulates Spatial Memory Retrieval - Xinyang Qi; Zhanhong Jeff Du; Lin Zhu; Xuemei Liu; Hua Xu; Zheng Zhou; Cheng Zhong; Shijiang Li; Liping Wang; Zhijun Zhang (Neuroscience Bulletin, 2019)

Sigma-1 receptor protects against endoplasmic reticulum stress-mediated apoptosis in mice with cerebral ischemia/reperfusion injury - Xuemei Zhao; Lin Zhu; Danyang Liu; Tianyan Chi; Xuefei Ji; Peng Liu; Xuexue Yang; Xinxin Tian; Libo Zou (Apoptosis, 2019)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

Responsibility modulates the neural correlates of regret during the sequential risk-taking task - Lin Li; Zhiyuan Liu; Huanghuang Niu; Li Zheng; Xuemei Cheng; Peng Sun; Fanzhi Anita Zhou; Xiuyan Guo (Experimental Brain Research, 2018)

Xanthoceraside modulates NR2B-containing NMDA receptors at synapses and rescues learning-memory deficits in APP/PS1 transgenic mice - Lin Zhu; Lei Yang; Xuemei Zhao; Danyang Liu; Xiaoli Guo; Peng Liu; Tianyan Chi; Xuefei Ji; Libo Zou (Psychopharmacology, 2018)

Modulation of financial deprivation on deception and its neural correlates - Peng Sun; Xiaoli Ling; Li Zheng; Jia Chen; Lin Li; Zhiyuan Liu; Xuemei Cheng; Xiuyan Guo (Experimental Brain Research, 2017)

Erratum to: Atmospheric Nitrogen Emission, Deposition, and Air Quality Impacts in China: an Overview - Xuejun Liu; Wen Xu; Lei Duan; Enzai Du; Yuepeng Pan; Xiankai Lu; Lin Zhang; Zhiyong Wu; Xuemei Wang; Ying Zhang; Jianlin Shen; Ling Song; et al. (Current Pollution Reports, 2017)

Atmospheric Nitrogen Emission, Deposition, and Air Quality Impacts in China: an Overview - Xuejun Liu; Wen Xu; Lei Duan; Enzai Du; Yuepeng Pan; Xiankai Lu; Lin Zhang; Zhiyong Wu; Xuemei Wang; Ying Zhang; Jianlin Shen; Ling Song; et al. (Current Pollution Reports, 2017)

Hippocampal size is related to short-term true and false memory, and right fusiform size is related to long-term true and false memory - Bi Zhu; Chuansheng Chen; Elizabeth F. Loftus; Qinghua He; Xuemei Lei; Qi Dong; Chongde Lin (Brain Structure and Function, 2016)

Perceived reputation of others modulates empathic neural responses - Li Zheng; Qianfeng Wang; Xuemei Cheng; Lin Li; Guang Yang; Lining Sun; Xiaoli Ling; Xiuyan Guo (Experimental Brain Research, 2016)

Butyrolactones derivatives from the fermentation products of a plant entophytic fungus Penicillium oxalicum - Lin Yuan; Wenzhong Huang; Kun Zhou; Yuede Wang; Wei Dong; Gang Du; Xuemei Gao; Yinhai Ma; Qiufen Hu (Natural Product Research, 2015)

Regression Analysis of Non-iatrogenic Factors That Determine Adherence to Radiation Therapy - Xiangzhao Bu; Xuemei Fan; Dawei Hao; Lin Guo; Chengjun Wu; Chong Zhou (Cell Biochemistry and Biophysics, 2015)

Incidental self-processing modulates the interaction of emotional valence and arousal - Qianfeng Wang; Li Zheng; Lin Li; Xiao Xu; Xuemei Cheng; Ruipeng Ning; Zoltan Dienes; Xiuyan Guo (Experimental Brain Research, 2015)

Urban Phosphorus Metabolism through Food Consumption - Gui‐Lin Li; Xuemei Bai; Shen Yu; Hua Zhang; Yong‐Guan Zhu (Journal of Industrial Ecology, 2012)
Summary Urbanization has significant impacts on local, regional, and global biogeochemical cycles, including through nutrient enrichment by food consumption, and especially in rapidly urbanizing countries. This article presents a time‐series estimation of phosphorus (P) metabolism through food consumption in Chinese cities and examines its relationship to income level during the period 1985–2006. Our results show that approximately 39% of the total dietary P inflow is exported through direct sewage discharge without treatment, 35% is exported via the output of solid human excreta, 7% is exported through sewage sludge landfill, and 19% is left within urban areas. The total inflow of dietary P to urban systems increases with per capita disposable income level. Furthermore, the ratio of dietary P remaining in urban systems to total dietary P inflow, the dietary P remaining in urban systems per capita, and the dietary P remaining per unit urban built‐up area respond in an inverted U shape to increases in per capita disposable income; the per capita outflow of dietary P shows a U‐shaped response. These relationships may indicate that the impact of urban dietary P on urban environmental systems follows the traditional environmental Kuznets curve, while the environmental impact of urban dietary P on surrounding nonurban ecosystems initially decreases but then increases with the rising income of urban residents.

Stereoselective toxicity of malathion and its metabolites, malaoxon and isomalathion - Anping Zhang; Xuemei Xie; Jing Ye; Chunmian Lin; Xiaoyan Hu (Environmental Chemistry Letters, 2011)

Entrainment of Intestinal Slow Waves with Electrical Stimulation Using Intraluminal Electrodes - Xuemei Lin; J. Hayes; L. J. Peters; J. D. Z. Chen (Annals of Biomedical Engineering, 2000)